Posner – Schlossman Syndrome: case report: Sindrome de Posner - Schlossman: reporte de caso - Mamani Maquera, Diego José (2021)
Introduction: Posner - Schlossman Syndrome (PSS) is a rare disease, more prevalent in men between 20 and 50 years old, characterized by recurrent attacks of anterior uveitis and ocular hypertension. Clinical case: We report the case of a 42-year-old patient with a single eye. He came to the consultation presenting decreased visual acuity, photobobia, halos around the lights, and intense pain in his left eye. The ophthalmological examination revealed inflammatory signs in the anterior segment, elevated intraocular pressure and damage to the optic nerve. Medical treatment was started with corticosteroids and topical antiglaucoma drugs, oral acetazolamide and intravenous mannitol, obtaining no response and it was decided to perform a surgical intervention (Ahmed valve implantation) in the left eye, subsequently achieving a good clinical evolution and resolution of the case. Conclusion: This report highlights that the episodic and recurrent nature of SPS requires strict monitoring.